1995
DOI: 10.1002/aja.1002030105
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of cardiac looping

Abstract: During the early stages of embryonic development, the heart is a smoothwalled, muscle-wrapped tube that bends and rotates in a vital, but poorly understood, morphogenetic process called looping. Since looping involves biomechanical forces, this paper examines two mechanically based hypotheses for the bending component of cardiac looping. The first hypothesis is that an initial tension in or near the dorsal mesocardium (DM), a longitudinal structure along the outside of the ventricle, drives the deformation. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 23 publications
(42 reference statements)
5
56
0
Order By: Relevance
“…This confirmed previous observations described in the rat embryo (Baldwin and Solursh, 1989). Our results (Linask et al, 2002(Linask et al, , 2003a, as well as those based on biomechanical considerations (Taber et al, 1995), indicated that the dorsal mesocardium, including the associated ECM, specifically asymmetric flectin within the dorsal mesocardial folds in the anterior heart field, also known as the secondary heart field, is an important area for specification of looping direction.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This confirmed previous observations described in the rat embryo (Baldwin and Solursh, 1989). Our results (Linask et al, 2002(Linask et al, , 2003a, as well as those based on biomechanical considerations (Taber et al, 1995), indicated that the dorsal mesocardium, including the associated ECM, specifically asymmetric flectin within the dorsal mesocardial folds in the anterior heart field, also known as the secondary heart field, is an important area for specification of looping direction.…”
Section: Resultssupporting
confidence: 92%
“…Cranially, these folds are continuous with the anterior splanchnic mesoderm, also known as the secondary (anterior) heart field to distinguish it from the primary fields giving rise to the left ventricle and part of the right (de la Cruz et al, 1989Cruz et al, , 1991Markwald et al, 1998;Waldo et al, 2001;Linask et al, 2002Linask et al, , 2003. Experimental evidence, as well as biomechanical considerations, suggested that the anterior dorsal mesocardial region, the adjacent foregut endoderm, and associated ECM are responsible for rendering directional cardiac looping (Taber et al, 1995;Linask et al, 2003a).…”
Section: Asymmetric Cell Proliferation Can Drive Cardiac Loopingmentioning
confidence: 99%
“…Looping is partly mediated by asymmetric gene and molecular expression [15,16], but animal models have also shown that mechanical forces play a major role in the looping process. Various hypotheses of mechanical looping mechanisms have been proposed, where experiments show that several redundant mechanisms are likely involved [17]. These include compressive axial forces as the heart tube lengthens [18], differential growth on either side of the tube [19], active cell shape change [14], cytoskeletal contractions [20] and extrinsic forces from neighbouring tissues [21].…”
Section: Introductionmentioning
confidence: 99%
“…Most investigators agree that heart development depends on both genetic and epigenetic factors, with the latter including the mechanochemical environment. Rapid progress is being made in defining the genetic and molecular factors that regulate looping (Brand, 2003;Harvey, 1998;Mercola and Levin, 2001;Srivastava and Olson, 1997), but the biophysical mechanisms that drive looping remain poorly understood (Männer, 2000;Taber et al, 1995). This review examines the role that biomechanics plays in the looping process.…”
Section: Introductionmentioning
confidence: 99%
“…First, many researchers have not fully appreciated (or been aware of) the need to consider both ventral bending and dextral rotation in interpreting experimental results. [As a novice to looping, even this author was not immune to this (Taber et al, 1995).] Although this characteristic of c-looping has been known for many years (Butler, 1952), Männer (2000) felt a need to reemphasize it.…”
mentioning
confidence: 99%